Exploring perceptions of extreme environments and extremophiles in Chilean schoolchildren: an ethnographic study - Rivera, Mailing; Fontana, Paola; Cortes, Wilson; Merino, Cristian; Vega, José Luis (Frontiers in Public Health, 2024)
Chile is unique because of its diverse extreme environment, ranging from arid climates in the north to polar climates in Patagonia. Microorganisms that live in these environments are called extremophiles, and these habitats experience intense ecosystem changes owing to climate warming. Most studies of extremophiles have focused on their biotechnological potential; however, no study has examined how students describe extremophiles. Therefore, we were interested in answering the following question: How do schoolchildren living in extreme environments describe their environments and extremophiles? We performed an ethnographic study and analyzed the results of 347 representative drawings of participants aged 12-16 years from three schools located in the extreme environments of Chile San Pedro de Atacama (hyper-arid, 2400 m), Lonquimay (forest, 925 m), and Punta Arenas (sub-Antarctic, 34 m). The social representation approach was used to collect data, and systemic networks were used to organize and systematize the drawings. The study found that, despite differences between extreme environments, certain natural elements, such as trees and the sun, are consistently represented by schoolchildren. The analysis revealed that the urban and rural categories were the two main categories identified. The main systemic networks were rural-sun (21,1%) for hyper-arid areas, urban-tree (14,1%) for forest areas, and urban-furniture (23,4%) for sub-Antarctic areas. When the results were analyzed by sex, we found a statistically significant difference for the rural category in the 7th grade, where girls mentioned being more rural than boys. Students living in hyper-arid areas represented higher extremophile drawings, with 57 extremophiles versus 20 and 39 for students living in sub-Antarctic and forest areas, respectively. Bacteria were extremophiles that were more represented. The results provide evidence that natural variables and semantic features that allow an environment to be categorized as extreme are not represented by children when they are focused on and inspired by the environment in which they live, suggesting that school literacy processes impact representations of their environment because they replicate school textbooks and not necessarily their environment.